피속 잡초 종자의 등온흡습곡선 특성 - 이용호(Yong Ho Lee); 변지영(Ji Young Byun); 나채선(Chae Sun Na); 김태완(Tae Wan Kim); 김정규(Jeong-Gyu Kim); 홍선희(Sun Hee Hong) (Weed & turfgrass science, 2015)
The equilibrium moisture contents (EMC) in seeds of four Echinochloa (E. crus-galli var. crus-galli, E. crus-galli var, echinata, E. crus-galli var. praticola, E. esculenta) were measured at $20^{°}C$ with equilibration over a series of lithium chloride solutions with relative humidities ranging from 0.11 to 0.8 to determine sorption isotherms and safe storage relative humidity. Standard seed sorption isotherm models i.e. modified Henderson, modified Chung-Pfost, modified Halsey, modified Oswin and Guggenheim-Anderson-deBoer (GAB) equations were adopted to evaluate the goodness of fit to sorption isotherms. This study indicated that EMC of seeds was significantly different in four Echinochloa species at various relative humidity. The modified Oswin equations for E. crus-galli var. crou-galli, E. crus-galli var, echinata, E. esculenta and GAB equation for E. crus-galli var. praticola were adequate models for the EMC data. Seeds of four Echinochloa species have monolayer moisture contents when stored at RH < 0.1. These results show that seed moisture isotherm model should be selected according to genetic variation.